A Companion to Medieval Miracle Collections
1 online resource.
Keywords: Miracle accounts provide a window into the views and conceptions of the laity, the uneducated, women, and even children, whose voices are mostly missing from other types of sources. They are not, however, simple to use. This volume offers a methodological insight into the medieval world of the miraculous. Consisting of 15 cutting-edge articles by leading scholars in the field, it provides versatile approaches to the origins, methods, and recording techniques of various types of miracle narratives. It offers fascinating case studies from across Europe, which show how miracle accounts can be used as a source for various topics such as lived religion, healing, protection, and family and gender. Contributors are Nicole Archambeau, Leigh Ann Craig, Ildikó Csepregi, Jussi Hanska, Emilia Jamroziak, Sari Katajala-Peltomaa, Jenni Kuuliala, Iona McCleery, Jyrki Nissi, Roberto Paciocco, Donald S. Prudlo, Marika Räsänen, Jonas Van Mulder, and Louise Elizabeth Wilson.